SÍNTESE E CARACTERIZAÇÃO DE ESTRUTURAS DO TIPO CORE/SHELL CoFe2O4@Ag OBTIDAS PELO MÉTODO SOLVATERMAL ASSISTIDO POR MICRO-ONDAS VISANDO APLICAÇÕES BIOLÓGICAS. - BORGES, Mikaelly Daiany Ferreira (2019)
Functionalised magnetic nanoparticles demonstrate wide industrial applicability and technological. In this context, this work aimed at the synthesis of nanoparticles CoFe2O4 by the microwave assisted thermal decomposition method using iron (III) trisacetylacetonate and cobalt (II) trisacetylacetonate in the presence of oleylamine, oleic acid and octadecene (CoFe2O4/AO/OL). The nanoparticles were characterized by Wavelength Dispersion Fluorescence Spectroscopy Techniques (WDXRF), X-Ray Diffractometry (DRX), Infrared Spectroscopy with Fourier Transform (FTIR), Raman Spectroscopy, Electronic Microscopy of Tranmission (MET), TG-DSC and Vibrant Sample Magnetometer (VSM) Nanoparticles were identified with single phase spatial group characteristics and crystalline structure of the like spinel. Rietveld's mathematical refinement treatment estimated that the size Average ferrite crystalite is approximately 6.64 nm, with low microdeformations in the order of 0.1%. The samples had superparamagnetic characteristics and the size average estimated by the Langevim equation proved to be very close to average size provided by the MET technique. To obtain CoFe2O4@Ag, initially performed the transfer of the nanoparticles to the aqueous phase using the cationic surfactant CTAB, such as transfer was verified by UV-vis. The silver coating of the nanoparticles was evaluated using DRX, which indicated diffraction peaks for silver and silver bromide metallic. Biological tests demonstrated potential fungicide of CoFe2O4@Ag, and cytotoxic in low doses to MCF-7 tumor cells.